Assessment for Learning Berorientasi Higher Order Thinking Skills untuk Menstimulus Kecakapan Literasi Numerasi - Khoiriah Khoiriah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This study aims to implement an assessment for learning oriented to higher order thinking skills to stimulate students' numeracy literacy skills. The research design used a pretest-posttest control group. The research sample involved two groups of students from twelve groups of eighth grade students at SMP Negeri 16 Bandar Lampung through random sampling. The data collection instruments were in the form of numeracy literacy skills test instruments and numeracy literacy skills observation instruments. Data were analyzed descriptively qualitatively and quantitatively with independent sample t test. The results of data analysis showed that the observation of students' numeracy literacy skills in the two experimental classes was categorized as